The Fig Tree at the End of the World: Reading Mark 11:12–25 and Enduring Creaturely Violence - Belloli, Jack (Journal for the study of the New Testament, 2025)
By establishing a horizon of contemporary ecological thought, this article seeks to offer a new ‘more-than-human’ interpretation of Mk 11.12–25. Rather than treating more-than-human perspectives simply as benign, universal solutions to all-too-human violence, this interpretation uses them as an invitation to explore the ethical complexity of how humans and nonhumans struggle to build a more liveable world together. Interpretations of Jesus’s curse of the fig tree have often come up against what Anna Lowenhaupt Tsing calls ‘the problem with scale’ in the face of environmental destruction, either sweeping over or overstating the curse’s potential ethical significance. This new interpretation draws on Tsing, alongside other recent ethnographers of more-than-human relations, to contextualise Jesus’s actions in relation to Mark’s representation of the Jerusalem temple as a site of exploitative resource extraction: human and nonhuman creatures fitfully resist this exploitation, but in ways which make their damage and competition inevitable. This interpretation is offered as distinctively Markan in its irresolution and irony, and recognising such irony signals new ways that the New Testament can resource a more granular environmental ethics.